A review of measurement of electromagnetic emission in electronic product: Techniques and challenges - Yuwono, Tito; Baharuddin, Mohd Hafiz; Misran, Norbahiah; Ismail, Mahamod; Mansor, Mohd Fais (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
Nowadays, electronic products are being used extensively in many fields and applications. The dense population of electronic devices in human life has become a challenge for microwave engineers to ensure that their products can meet the Electromagnetic Compatibility (EMC) standards. Complex electronic products with smaller sizes and denser components will be a challenge for compliance with EMC standards. In addition, the occurrence of non-stationary emission at certain operating modes becomes a challenge for analysis. Error in analyzing EM emissions will make the products unable to meet the requirements of EMC standards; hence, they will be prohibited to be marketed. Currently, there are two methods of emission analysis, i.e. by measurement and modeling or computation. There are some problems, however, in the analysis of EM emissions regarding the area of test, complexity, DUT positioning error, installation cost, and time consumption. In this paper, the analysis techniques for EM emissions including Open Area Test Site (OATS), Anechoic chamber, Transverse Electromagnetics TEM Cell, Compact Antenna Test Range (CATR) and near field scanning are reviewed comprehensively. This survey covered EMC standards, principles of EM emission measurement techniques, advantages and disadvantages of EM emission measurement techniques, studies and applications of each technique, recommendations for which technique to be used, and challenges for future research in EM emission measurement. The final section of this paper discusses the challenges for near-field measurements related to the non-stationary emissions phenomenon. This papers also presents the challenges of how to detect and characterize them.